An Experimental Plan: Teaching of Astronomical Clock Tower under View of New Liberal Arts Perspective - Jianguang Yao; Lingfei Chen (Journal of Educational Issues, 2024)
At the end of the 11th century, the “Astronomical Clock Tower” developed by Su Song’s team involved many scientific knowledge, advanced and complex technologies, and created many world firsts. It played an important role in the history of science and technology in China and even the world. It was the best test sample for exploring the teaching method of the history of science and technology content in the teaching reform of the undergraduate history (normal) major “Ancient Chinese History” course under the guidance of the new liberal arts and science concept. The experimental plan focuses on the common characteristics of this type of content, closely adheres to teaching objectives, fits the actual learning situation, and is based on general teaching conditions. Within the limit of class hours, it introduces the background, structure, and function, explains the principle and process of key components, analyzes ideas and methods, highlights the key points and difficulties, and strives to be interesting, easy to understand, and memorable, so that students can feel the outstanding wisdom and innovation of the sages, clarify its position and influence in the history of science and technology in China and the world, and accumulate knowledge and methods for future teaching of this type of historical content.